ANALYSIS OF FAIR VALUE MEASUREMENT ON INVESTMENT PROPERTY AND ITS EFFECT ON FINANCIAL PERFORMANCE - M. Shabri Putra R (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
Fair value measurement of investment properties has become a critical issue in financial reporting, particularly under IFRS 13 and IAS 40, as it directly influences transparency, comparability, and decision-making by stakeholders. This study investigates the relationship between fair value measurement and financial performance in publicly listed real estate firms. A qualitative research design was employed, combining semi-structured interviews with twenty industry professionals and financial analysis of fifteen investment properties across commercial, residential, and mixed-use sectors. Data were triangulated through thematic analysis and a review of financial statements, focusing on net operating income (NOI), return on investment (ROI), and cash flow. The findings reveal that fair value measurement enhances financial performance by producing higher ROI and NOI compared with historical cost methods, although it also introduces greater volatility in financial reporting. Market-based approaches were perceived as more reflective of current conditions, while income-based approaches provided stability at the cost of reduced transparency. Additionally, technological tools such as data analytics and artificial intelligence were identified as promising in reducing subjectivity and improving valuation accuracy. The study contributes to the literature by integrating qualitative insights and financial data to highlight the trade-offs between transparency, stability, and reliability in fair value reporting. Practically, the results provide guidance for investors, regulators, and practitioners in strengthening valuation practices and enhancing decision-making. Future research should expand the scope through longitudinal and cross-country analyses to deepen understanding of fair value adoption in diverse regulatory environments.